Zooplankton vertical stratification in the East-pacific and Indian sectors of the Southern Ocean - Liu, Yunzhe; Wang, Yanqing; Sun, Yongming; Yang, Guang; Swadling, Kerrie M. (Frontiers in Marine Science, 2024)
Introduction In the Southern Ocean, the large-scale distribution of zooplankton, including their abundance and community composition from the epipelagic to the upper bathypelagic layers, remains poorly understood. This gap in knowledge limits our comprehension of their ecological and biogeochemical roles. Methods To better understand their community structure, depth-stratified zooplankton samples were collected from 0 to 1500 m during four summers in the East-Pacific and Indian sectors of the Southern Ocean. In addition, analysis of environmental drivers including temperature, salinity, dissolved oxygen, and chlorophyll a concentration, as well as water masses was conducted. Results Our study indicates that zooplankton diversity may be similar between the two sectors, while zooplankton abundance was higher in the East-Pacific sector during different sampling months and years. Moreover, zooplankton abundance decreased with depth in both sectors. Based on cluster analysis, zooplankton communities were generally divided by either the epipelagic or the deeper layers’ communities. In both sectors, the epipelagic layer was dominated by cyclopoid copepods, such as Oithona similis and Oncaea curvata, as well as calanoid copepods including Calanoides acutus, Rhincalanus gigas, and Ctenocalanus citer, while copepods and other taxa including Chaetognatha, Amphipoda, and Ostracoda, were important contributors to the deep layer communities. Discussion Our analysis revealed that water masses, combined with their physical characteristics such as specific temperature and salinity ranges and depth, along with biological factors such as chlorophyll a concentration, might be the most important drivers for structuring zooplankton communities from epipelagic to upper bathypelagic layer.